2017
DOI: 10.1007/jhep12(2017)060
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of |Vcb| from B → D(∗)ℓνℓ and the Standard Model predictions of R(D(∗))

Abstract: We extract |V cb | from the available data in the decay B → D ( * ) ν . B → D * ν , the unfolded binned differential decay rates of four kinematic variables including the q 2 bins have been used. In the CLN and BGL parameterizations of the form factors, the combined fit to all the available data along with their correlations yields |V cb | = (39.77 ± 0.89) × 10 −3 and (40.90 ± 0.94) × 10 −3 respectively. In these fits, we have used the inputs from lattice and light cone sum rule (LCSR) along with the data. Usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
222
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(242 citation statements)
references
References 24 publications
17
222
3
Order By: Relevance
“…Measurements from BaBar, Belle, and LHCb of the ratios R(D ( * ) ) [10][11][12][13][14][15][16][17][18][19] of the heavy-light meson decays B → D ( * ) ν, with = τ to = µ, exhibit a combined 3.1σ discrepancy from the HFLAV-suggested [20], which average Refs. [6,[21][22][23]. Recently, the LHCb collaboration has measured R(J/ψ) [24], which is within 1.3σ [25] of the SM prediction.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Measurements from BaBar, Belle, and LHCb of the ratios R(D ( * ) ) [10][11][12][13][14][15][16][17][18][19] of the heavy-light meson decays B → D ( * ) ν, with = τ to = µ, exhibit a combined 3.1σ discrepancy from the HFLAV-suggested [20], which average Refs. [6,[21][22][23]. Recently, the LHCb collaboration has measured R(J/ψ) [24], which is within 1.3σ [25] of the SM prediction.…”
Section: Introductionmentioning
confidence: 59%
“…The constraint of unitarity in model-independent approaches such as the BGL parametrization has historically been underutilized, because fits to experiment typically consider only a single exclusive process (e.g., B → D * ν). However, each exclusive channel appearing in the two-point Green's function for b → c currents positively contributes to the unitarity bound, and therefore a simultaneous fit including multiple processes provides stronger constraints on each of the individual processes [6,23,37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found, however, that the low exclusive value might actually be a problem originating in the use of a certain form factor parametrization in the experimental analysis. 8 Using the Boyd, Grinstein, Lebed (BGL) parametrization one finds values that lie considerably closer to the inclusive one, see [143][144][145][146]. Currently, there are various determinations of V cb available: …”
Section: Appendix D: Ckm Dependencementioning
confidence: 99%
“…Hereafter,B → D ( * ) τ −ν τ [4] and B → D ( * ) −ν will be referred to as the signal and normalization modes, respectively. The SM calculations for these ratios, performed by several groups [5][6][7][8], are averaged by HFLAV [9] to obtain R(D) = 0.299 ± 0.003 and R(D * ) = 0.258 ± 0.005. Semitauonic B decays were first observed by Belle in 2007 [10], with subsequent studies reported by Belle [11][12][13][14], BaBar [15], and LHCb [16,17].…”
mentioning
confidence: 99%